Evaluation of high-value bioproducts production by marine endophytic fungus Arthrinium sp. FAKSA 10 under solid state fermentation using agro-industrial wastes - Mohammad J. Alsarraf; Fuad Ameen; Abdullah Alfalih; Zirak Sajjad (Electronic Journal of Biotechnology)
Background: To address public health challenges, there is increasing interest in bioactive metabolites from unconventional sources for targeted cancer and viral treatments with minimal side effects. Endophytic fungi are promising for these therapies. This study focused on maximizing bioactive agent yields from these fungi using a low-cost medium and optimized fermentation system. Results: Forty-three endophytic fungi isolated from Sinularia polydactyla were cultivated on wheat bran medium and evaluated for bioactive metabolites under solid-state fermentation. Strain FAKSA 10, identified as Arthrinium sp. FAKSA 10, exhibited the highest levels of pharmaceutical metabolites, including L-glutaminase, L-methioninase, L-arginase, L-asparaginase, L-tyrosinase, L-lysine α-oxidase, and ribonuclease, with a 79.12% hepatitis C virus knockdown rate. This strain produced 46 metabolites with anticancer, antioxidant, antiviral, and cytotoxic properties, including major compounds like hexadecanoic acid methyl ester; hexadecanoic acid ethyl ester; 9, 12-octadecadienoic acid (Z, Z), methyl ester; 9-octadecenoic acid (Z)-, methyl ester, and 11, 14-eicosadienoic acid, methyl ester. A cost-effective strategy using 11 agro-industrial residues was applied, followed by optimization of the solid-state fermentation system. This optimization increased enzyme yields and enhanced antiviral and antioxidant activities. The optimal conditions for solid-state fermentation were a 10 d incubation, 1 mm particle size, 60% initial moisture, 28 °C temperature, and 2 × 107 CFU/mL inoculum size. Conclusions: This study exploited Arthrinium sp. FAKSA 10 metabolites as natural pharmaceuticals against cancer and viral diseases, highlighting their significant antioxidant properties. Among various residues, oil cakes emerged as an effective and cost-efficient medium, capable of significantly enhancing the production of valuable bioactive metabolites.How to cite: Alsarraf MJ, Ameen F, Alfalih A, et al. Evaluation of high-value bioproducts production by marine endophytic fungus Arthrinium sp. FAKSA 10 under solid state fermentation using agro-industrial wastes. Electron J Biotechnol 2025;73. https://doi.org/10.1016/j.ejbt.2024.09.001.